2021
DOI: 10.1007/978-3-030-86436-1_7
|View full text |Cite
|
Sign up to set email alerts
|

Analysing Peer Assessment Interactions and Their Temporal Dynamics Using a Graphlet-Based Method

Abstract: Engaging students in peer assessment is an innovative assessment process which has a positive impact on students learning experience. However, the adoption of peer assessment can be slow and uncomfortably experienced by students. Moreover, peer assessment can be prone to several biases. In this paper, we argue that the analysis of peer assessment interactions and phenomena can benefit from the social network analysis domain. We applied a graphlet-based method to a dataset collected during in-class courses inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Djelil et al [34] performed a study involving 48 university students in higher education. Although the sample size was relatively small, they found that following an adaptation period, during which students initially preferred assessment by teachers or known peers, they gradually developed more positive attitudes towards peer assessment.…”
Section: Student Perceptions Of Peer Assessmentmentioning
confidence: 99%
“…Djelil et al [34] performed a study involving 48 university students in higher education. Although the sample size was relatively small, they found that following an adaptation period, during which students initially preferred assessment by teachers or known peers, they gradually developed more positive attitudes towards peer assessment.…”
Section: Student Perceptions Of Peer Assessmentmentioning
confidence: 99%